Enhancing Science Learning Outcomes through Quantum Teaching Method at Grade VI Students of SD Negeri 11 Koto Salak - Muryanti, Muryanti (TOFEDU: The Future of Education Journal, 2023)
The condition of mathematics learning to date is still dominated by teachers as providers of knowledge, resulting in students getting more information from teacher explanations alone, resulting in students’ thinking being less developed. The impact of this learning is that mathematics learning outcomes are not optimal. Question Students Have is a strategy that encourages students to dare to ask questions in written form. The aim of this research is to determine the learning outcomes of students taught using the Question Students Have strategy for Class VI students at SDN 11 Koto Salak. The type of research used in this research is experimental research, namely Pre Experimental with a One Group Pre-test and Post-test research design. The sample for this research was 23 Class VI students at SDN 11 Koto Baru, Dharmasraya Regency. The research instruments used in this research were student learning outcomes tests, documentation and observation sheets. The data analysis technique used is descriptive statistical analysis with the PTK cycle. The research results show an increase in student learning outcomes in mathematics lessons seen from the class average score. The value before intervention was 39.78%. The value in cycle I increased to 67.82% and there was another increase in cycle II to 82.40%. Based on these results, it is concluded that the Question Students Have strategy can improve mathematics learning outcomes for class VI students at SDN 11 Koto Salak.